Effect of passive exposure to cigarette smoke on blood pressure in children and adolescents: a meta-analysis of epidemiologic studies - Mahshid Aryanpur; Mahmoud Yousefifard; Alireza Oraii; Gholamreza Heydari; Mehdi Kazempour-Dizaji; Hooman Sharifi; Mostafa Hosseini; Hamidreza Jamaati (BMC, 2019)
Abstract Background Hypertension is an emerging disease in children and adolescents resulting in future morbidities. Cigarette smoking is one of the most studied contributing factors in this regard; however, there are contradictory results among different studies. Therefore, the present meta-analysis tends to assess the relationship between passive exposure to cigarette smoke and blood pressure in children and adolescents. Method Medline, Embase, Scopus, EBSCO, and Web of Sciences were systematically reviewed for observational studies up to May, 2017, in which the relationship between cigarette smoking and hypertension were assessed in children and adolescents. The meta-analysis was performed with a fixed effect or random effects model according to the heterogeneity. Results Twenty-nine studies were included in present meta-analysis incorporating 192,067 children and adolescents. Active smoking (pooled OR = 0.92; 95% CI: 0.79 to 1.05) or passive exposure to cigarette smoke (pooled OR = 1.01; 95% CI: 0.93 to 1.10) were not associated with developing hypertension in the study population. Despite the fact that active cigarette smoking did not significantly affect absolute level of systolic and diastolic blood pressure, it was shown that passive exposure to cigarette smoke leads to a significant increase in absolute level of systolic blood pressure (pooled coefficient = 0.26; 95% CI: 0.12 to 0.39). Conclusion Both active and passive cigarette smoking were not associated with developing hypertension in children and adolescents. However, passive cigarette smoke was associated with higher level of systolic blood pressure in children and adolescents.